Pelatihan Kewirausahaan Rumah Tangga: Membangun Usaha Rumahan Modal Kecil dengan Hasil Maksimal - Diana, Fina; Ridwan, Ridwan; Ilham, Ilham; Murniati, Murniati (Universitas Patria Artha, 2025)
This Community Service (PKM) activity aims to empower housewives in Bangkala Village, Manggala District, Makassar City through home entrepreneurship training. This training focused on improving knowledge, skills, and motivation in building home businesses with small capital but maximum results. The results of the activity showed an increase in participants' understanding of the concepts of entrepreneurship, business management, and digital marketing. Participants generated various business ideas such as cookies, trendy drinks, and handicrafts. This activity succeeded in fostering an entrepreneurial spirit and encouraging the birth of new entrepreneurs at the household level. The main conclusion from this material is that small capital home businesses have great potential to grow if supported by creativity, good management, the right marketing strategy, and a willingness to start from small steps. The motivational message conveyed is 'Great success always begins with small steps